2006
DOI: 10.1111/j.1468-2885.2006.00272.x
|View full text |Cite
|
Sign up to set email alerts
|

Checking the Map: Critiquing Joanne Martin's Metatheory of Organizational Culture and Its Uses in Communication Research

Abstract: Joanne Martin's scholarship has significantly influenced the study of organizational culture by communication scholars. Martin's recent metatheory seeks to ''map'' the ''terrain'' of perspectives commonly used to study organizational culture and argues for the use of multiple perspectives to produce more fruitful research. While acknowledging the benefits of this metatheory, we critique 2 of its problematic elements. Both arise from Martin's claims about the phenomena of organizational culture and the various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Following Taylor, Irvin, and Wieland (), Keyton () argued that Fairhurst and Putnam's () grounded‐in‐action orientation underscored the limitations of Martin's (, ) tripartite approach of integration, differentiation, and fragmentation by encouraging researchers to ask, “How is organizational culture grounded in the flow of discourse practices of organizational members?” To embrace this orientation, scholars then needed to situate “integration, differentiation, and fragmentation as heuristic classifications of ontologically hybrid phenomena that [were] not reducible to cognitive perspectives” (Taylor et al, , p. 324). This reconceptualization of organizational culture, based on the Fairhurst and Putnam () framework, was significant not only because it provided a basis for analyzing and classifying existing literatures but also because it reformulated theoretical classifications that theorists often treated as static and discrete.…”
Section: Tracing Applications Of This Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Following Taylor, Irvin, and Wieland (), Keyton () argued that Fairhurst and Putnam's () grounded‐in‐action orientation underscored the limitations of Martin's (, ) tripartite approach of integration, differentiation, and fragmentation by encouraging researchers to ask, “How is organizational culture grounded in the flow of discourse practices of organizational members?” To embrace this orientation, scholars then needed to situate “integration, differentiation, and fragmentation as heuristic classifications of ontologically hybrid phenomena that [were] not reducible to cognitive perspectives” (Taylor et al, , p. 324). This reconceptualization of organizational culture, based on the Fairhurst and Putnam () framework, was significant not only because it provided a basis for analyzing and classifying existing literatures but also because it reformulated theoretical classifications that theorists often treated as static and discrete.…”
Section: Tracing Applications Of This Frameworkmentioning
confidence: 99%
“…Following Taylor, Irvin, and Wieland (2006), Keyton (2014) argued that Fairhurst and Putnam's (2004) grounded-in-action orientation underscored the limitations of Martin's (1992Martin's ( , 2002 tripartite approach of integration, differentiation, and fragmentation by encouraging researchers to ask, "How is organizational culture grounded in the flow of discourse practices of organizational members?" To embrace this orientation, scholars then needed to situate "integration, differentiation, and fragmentation as heuristic classifications of ontologically hybrid phenomena that [were] not reducible to cognitive perspectives" (Taylor et al, 2006, p. 324).…”
Section: Tracing Applications Of This Frameworkmentioning
confidence: 99%
“…Because organizational values encompass a broad range of phenomena (e.g., values are usually investigated from multiple perspectives as elements of organizational identity and culture processes, AMR, 2000;Taylor, Irvin & Wieland, 2006), the scope of this paper narrows down to a study of the performative qualities of values for two reasons. Firstly, by focusing solely on exploring different theorizations of organizational values, this paper develops a conceptualization of values that problematizes (Alvesson & Sandberg, 2011) a dominant dichotomy between words and actions and the cause-effect rationale for the purpose of providing novel avenues for future management research.…”
Section: Introductionmentioning
confidence: 99%
“…Findings from the study indicated gender norms such as the "boys will be boys" rhetoric were highly reinforced among media coverage of the incident (Kasinsky 1998). People are generally a part of multiple cultures. Being a part of multiple cultures can cause differentiation when there is conflict between those cultures, which can then skew the way that an individual views the organization (Taylor et al 2006). When a person joins the military, they are still a part of the cultures they identified with before they joined.…”
Section: Organizational Culturementioning
confidence: 99%